Can it wait? A systematic review of immediate vs. delayed surgical repair of penile fractures - Wong, Nathan Colin; Dason, Shawn; Bansal, Rahul K.; Davies, Timothy O.; Braga, Luis H. (Canadian Urological Association Journal, 2017)
Introduction: Penile fractures have classically been thought to require immediate surgical intervention; however, recent series have described acceptable outcomes with delayed repair. In this systematic review, we compared complication rates between immediate and delayed repair of penile fractures. Methods: A systematic search of MEDLINE, Embase, CENTRAL, and Web of Science was performed with predefined search terms between 1974 and 2015. Titles and abstracts were screened prior to full-text review and quality appraisal by two independent investigators. Abstracted outcomes included postoperative erectile dysfunction (ED), tunical scar formation, and penile curvature. Only studies reporting a direct comparison of complications following immediate (<24 hours from injury to presentation/surgery) and delayed (>24 hours) repair of penile fractures were included. Results: A total of 12 studies met inclusion criteria. All were retrospective, observational studies of low or moderate methodological quality. Of the reported 502 patients, 391 underwent immediate repair and 111 delayed repair. In the immediate repair group, the percent of patients with postoperative ED, tunical scars, and curvature were 6.6%, 5.4%, and 1.8%, respectively, while in the delayed group, the rates of ED, tunical scars, and curvature were 4.5% across the board. Rates of ED and tunical scar formation following immediate compared to delayed repair trended towards favouring immediate repair, but did not differ significantly, while rates of curvature significantly favoured immediate repair. However, cases of curvature were typically reported as mild and none affected sexual functioning. Conclusions: In this systematic review, we demonstrated that ED and tunical scar formation rates between immediate and delayed repair of penile fractures were statistically similar, while immediate repair had a lower rate of penile curvature. Although this suggests that a brief delay in repair may be acceptable in select patients, the results should be interpreted with caution, as the included studies were of low or moderate methodological quality. Most importantly, this review highlights the deficiencies in the current penile fracture literature, setting the stage to improve the quality of future studies.